IDENTIFIKASI KEMAMPUAN MENULIS TEKS BIOGRAFI DALAM PEMBELAJARAN DARING BERBASIS MODEL THINK TALK WRITE (TTW) - Meiyanti Melawati Putri; Indra Permana; Yeni Rostikawati (IKIP Siliwangi, 2023)
Online learning is distance learning taught by teachers and students through internet network access and is commonly referred to as online (online). One of the difficulties of learning online is learning the skills of writing biographical texts. Students still determine the structure of speech and the difficulty of using the correct biographical text. Therefore, this study was conducted using the TTW model in online learning to determine student learning outcomes in learning to write biographies and facilitate the improvement of biographical writing. The sample of this study was taken from class X science 4 students of SMA Negeri 4 Cimahi, totaling 20 students. The research method used is a qualitative descriptive method, in which the survey results are described by compiling the scores obtained. The results of this study can be seen from the learning outcomes of students in writing biographies, with four students with the highest scores and 16 other students with moderate grades. The grade point average for all students is 85. From these results, it can be concluded that the use of the TTW learner model is suitable to be applied to biographical text materials for class X high school students in online learning.